STORAGE OF FREE AMINO ACIDS IN ASCARIDIA GALLI, A DOMESTIC FOWL NEMATODE PARASITE - NANWARE, SANJAY SHAMRAO; BALDE, GOVIND HANMANTRAO (The Bioscan, 2010)
Free amino acids in Ascaridia galli (Schrank, 1788), Freeborn, 1923 parasitizing domestic fowl host play a very important role in the production of energy by acting as catalysts for various metabolic processes. A.galli live in an environment which is rich in protein and free amino acid content. These nematodes have a very free access for the uptake and absorption of the said molecules Shishova and Lev, (1970). Hence in this investigation the study of free amino acids content level is very helpuful to understanding to some extent the free amino acid synthesis capacity of nematode parasites i.e. Ascaridia galli (Schrank,1788), Freeborn, 1923 from Nanded region (M.S.) India. In present investigation storage of free amino acids in male is 112.09 ± 15.97 and in female is 169.00 ± 27.23 μg/100 mg tissue respectively.